Identification and evolutionary analysis of the metal‐tolerance protein family in eight Cucurbitaceae species. Issue 1 (6th November 2021) - Jiang, Xinchen; Yin, Junliang; Wang, Lixin; Xi, Keyong; Zhu, Xiongmeng; Li, Gang; Zhu, Yongxing; Liu, Yiqing
Abstract: Metal‐tolerance proteins (MTPs) are divalent cation transporters and play fundamental roles in plant metal tolerance and ion homeostasis. Despite that, a systematic investigation of MTPs in Cucurbitacea is still lacking. In this study, 142 MTPs were identified from 11 released genomes of 8 Cucurbitaceae species. They were phylogenetically separated into three clusters (Zn‐cation diffusion facilitator proteins [CDFs], Fe/Zn‐CDFs, and Mn‐CDFs) and further subdivided into seven groups (G1, G5, G6, G7, G8, G9, and G12). Characterization analysis revealed that most MTPs were plasma membrane‐located hydrophobic proteins. Motif and exon/intron analysis showed that members in the same group contained similar conserved motifs and gene structures. Moreover, 98 pairs of segmental‐like duplication events were found. The nonsynonymous/synonymous substitution ratios between each pair were less than 1, implying that Cucurbitaceae MTPs were under purification selection. Expression profiling suggested that several MTP genes, such as CsCLMTP1, CmeMTP3, LsMTP3, and Cl97103MTP3, were constitutively expressed in corresponding Cucurbitaceae species, and their expression levels were not significantly altered by NaCl, drought, or pathogen infection. The expression patterns of cucumber MTP genes under Zn 2+, Cu 2+, Mn 2+, and Cd 2+ stress were studied by quantitative real‐time polymerase chain reaction and the results showed that these MTPs were induced by at least one metal ion, suggesting their involvement in metal tolerance or transportation. The identification and comprehensive investigation of MTP family members will provide a basis for the analysis of ion transport functions and ion tolerance mechanisms of Cucurbitaceae MTPs. Core Ideas: A total of 142 metal‐tolerance proteins (MTPs) were identified in eight Cucurbitaceae species. Cucurbitaceae MTPs were under strong purification selection. Cucurbitaceae MTPs showed tissues and treatment‐specific expression patterns. Cucumber MTPs were induced by metal ions.